Antioxidant Compound of Curcuma mangga Val. with Variation in Rhizome Parts and Soil Types - Nuurachmawati, Uningtya; Pujimulyani, Dwiyati; Tamaroh, Siti; Windrayani, Emi (Indonesian Food and Nutrition Progress, 2024)
The scientific name of Curcuma mangga Val. (CM), that is commonly known as temu mangga, contains polyphenols, categorized as antioxidant compounds. These antioxidant compounds can neutralize free radicals. The study aims to determine the influence of rhizome parts and soil types on the antioxidant properties of CM. The research stages include sorting, peeling, washing, blanching, drying, and compositional analysis (antioxidant activity, total phenolic, flavonoid, and tannin). The study utilized a Completely Randomized Design (CRD) with rhizome parts (main, 1st tiller, and 2nd tiller) and soil types (clay, lime, and sand) as variables. Both rhizome part and soil type have significant effects on the antioxidant activity and antioxidant compounds of CM. The chosen CM, specifically the main rhizome with clay soil type, exhibits an antioxidant activity of 82.50% RSA, total phenolic of 647.50 mg GAE/100 g db, flavonoids of 620.2 mg QE/100 g db (dry basis), and tannins of 167.07 mg CE/100 g db.